PERANAN PENASEHAT HUKUM DALAM MEWUJUDKAN KEADILAN - ahkam jayadi (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2018)
Law No. 48 of 2009 concerning Judicial Power has affirmed that the judicial process is carried out based on principles,